The Representation Of Women's Resistance In The Film “Perempuan Tanah Jahanam” - Nindi putri; Endang, Anis; Risdiyanto, Bayu (Social Sciences Journal, 2024)
This study was conducted to analyze the representation of resistance by women in the horror film "Perempuan Tanah Jahanam". Apart from being a form of mass communication media that describes people's social life, film is also a cultural creation that brings important values to the audience, for example regarding issues about women. This study uses a qualitative descriptive approach with analysis of Roland Barthes semiotic model. The focus of this research is to look for markers, markers and signs in 5 scenes that show resistance. Data collection techniques used are documentation, literature study, and observation. The result of this research is that women's resistance is shown as a phenomenon that refers to social situations. The aggrieved parties in the social structure of society fight against those who harm them. The ideology contained in the film is the ideology of Postmodern Feminism. Feminism of this school avoids terms that imply the existence of a unity that limits differences. Postmodern feminism opposes characteristics in an effort to resolve women's oppression. The film "Perempuan Tanah Jahanam" is a form of women's rebellion against social reality. This school of thought clarifies itself as postmodern feminists who try to avoid any action that will restore male construction.